The Influence of Digital Leadership and Organizational Agility on Firm Performance: Evidence from Indonesian Mid-Sized Companies - Bagas Pratama Nugroho; Siti Rahmawati Putri; M Zainul Hafizi (Journal of Economics and Management, 2025)
This study examines the influence of digital leadership and organizational agility on firm performance in Indonesian mid-sized companies. Rapid digital disruption forces firms in emerging economies to strengthen leadership capabilities and adaptive capacity to sustain performance. This research adopts a quantitative approach using survey data collected from managers of mid-sized firms across service and manufacturing sectors in Indonesia. Data are analyzed using structural equation modeling to test direct and indirect relationships among variables. The findings show that digital leadership has a significant positive effect on organizational agility and firm performance. Organizational agility also demonstrates a strong positive impact on firm performance and partially mediates the relationship between digital leadership and performance outcomes. These results confirm dynamic capability theory, which emphasizes leadership and agility as critical mechanisms for navigating digital transformation. The study contributes empirically by clarifying how digital leadership translates into performance advantages through agile organizational processes in the context of developing economies. Practically, the findings suggest that managers should invest in digital-oriented leadership development and agile structures to improve responsiveness, decision speed, and competitive performance. This study provides relevant insights for scholars and practitioners seeking to understand performance drivers in digitally transforming mid-sized firms in Indonesia.